CO2 CAPTURE AND STORAGE IN CONCRETE GENERATED THROUGH EARLY-AGE CABONATION OF CALCIUM SILICATE HYDRATE (Nonconventional Technologies Review, 2025)
Recent global research on the sequestration and definitive storage of CO2 into concrete due to untimely carbonation of hydrated Ca2SiO4 (known as C-S-H), the most important phase of ordinary cement, has piqued the interest of authors of this paper. Limiting the gas footprint released into the atmosphere remains a very topical objective in the world and implicitly, also of the authors. Sodium bicarbonate (NaHCO3) added into starting mix as a partial substitute for cement has already been identified as the suitable option to reach the objective. Another very interesting effect has been experimentally highlighted in the direction of increasing the mechanical resistance particularly, at an early-age of the concrete preparation. Specific measurements carried out after only 6 hours has found very high values ​​of compression and flexural strength, close to the values ​​corresponding to the end of concrete curing process of 28 days. This procedure has not yet been finalized in technological terms in the world. Its importance lies in the possibility of manufacturing without CO2 emissions and utilizing the traditional Portland cement as the main binder for construction concrete in the current situation of world environmental crisis.
Keywords: CO2 sequestration; C-S-H; untimely carbonation; sodium bicarbonate; cement; mechanical strength